Genetic resistance to gastrointestinal nematode parasites in Red Maasai sheep in Kenya - Baker, R.L.; Mwamachi, D.M.; Audho, James O.; Thorpe, W.R. (1994)
This study is evaluating the resistance of Red Maasai sheep to endoparasite infections relative to Dorper sheep and a range of Red Maasai x Dorper crosses. The results confirm previous reports that both Red Maasai ewes and lambs are more resistant to endoparasites (predominantly Haemonchus contortus) than Dorper sheep. Resistance was shown by the ability of the Red Maasai to maintain higher packed cell volume levels (i.e. to resist anaemia), lower faecal egg counts and markedly lower lamb mortality. Heritabilities for PCV and FEC in lambs were low at weaning (3 months of age) but ranged from 0.20 to 0.30 for FEC in 10-month old lambs. From a preliminary assessment of total flock productivity it is found that sheep producers could double their lamb off-takes if they used Red Maasai or Red Maasai-crosses instead of Dorpers.